2017
DOI: 10.1002/ana.24992
|View full text |Cite
|
Sign up to set email alerts
|

Brain microvascular injury and white matter disease provoked by diabetes‐associated hyperamylinemia

Abstract: Objectives The brain blood vessels of patients with type-2 diabetes and dementia have deposition of amylin, an amyloidogenic hormone co-secreted with insulin. It is not known whether vascular amylin deposition is a consequence or a trigger of vascular injury. We tested the hypothesis that the vascular amylin deposits cause endothelial dysfunction and microvascular injury and are modulated by the amylin transport in the brain via plasma apolipoproteins. Methods Rats overexpressing amyloidogenic (human) amylin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
149
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(159 citation statements)
references
References 54 publications
10
149
0
Order By: Relevance
“…They noted pancreatic amylin‐Aβ and amylin‐tau deposits in humans with AD in the absence of type 2 diabetes, which the authors interpreted as potential evidence for a role of Aβ and tau tangle pathology in insulin resistance in these subjects. We suggest an alternative interpretation of this finding that we base on 4 key observations: (1) pancreatic β cells express and process both the Aβ protein precursor and tau mRNAs, implying that amylin‐Aβ and amylin‐tau inclusions may originate from the pancreas; (2) affected age‐groups and clinical trajectories in type 2 diabetes and late onset AD generally indicate that diabetes most commonly precedes AD and is associated with an acceleration of the transition from mild cognitive impairment to dementia; (3) consistent with this observation and because rodent amylin is nonamyloidogenic, rodent AD models do not develop type 2 diabetes, whereas pancreatic expression of amyloid‐forming human amylin in non‐AD rats causes type 2 diabetes, brain amylin deposition, and behavior deficits; and (4) the brain region involved in the central regulation of pancreatic β‐cell function (ie, the hypothalamus) is affected by AD pathology. Consequently, AD may impair central signaling pathways that regulate amylin secretion, leading to pancreatic β‐cell dysfunction and impaired clearance of amylin, Aβ, and tau.…”
mentioning
confidence: 68%
“…They noted pancreatic amylin‐Aβ and amylin‐tau deposits in humans with AD in the absence of type 2 diabetes, which the authors interpreted as potential evidence for a role of Aβ and tau tangle pathology in insulin resistance in these subjects. We suggest an alternative interpretation of this finding that we base on 4 key observations: (1) pancreatic β cells express and process both the Aβ protein precursor and tau mRNAs, implying that amylin‐Aβ and amylin‐tau inclusions may originate from the pancreas; (2) affected age‐groups and clinical trajectories in type 2 diabetes and late onset AD generally indicate that diabetes most commonly precedes AD and is associated with an acceleration of the transition from mild cognitive impairment to dementia; (3) consistent with this observation and because rodent amylin is nonamyloidogenic, rodent AD models do not develop type 2 diabetes, whereas pancreatic expression of amyloid‐forming human amylin in non‐AD rats causes type 2 diabetes, brain amylin deposition, and behavior deficits; and (4) the brain region involved in the central regulation of pancreatic β‐cell function (ie, the hypothalamus) is affected by AD pathology. Consequently, AD may impair central signaling pathways that regulate amylin secretion, leading to pancreatic β‐cell dysfunction and impaired clearance of amylin, Aβ, and tau.…”
mentioning
confidence: 68%
“…Another study also found deleterious microvascular effects of hyperamylinaemia, finding disruption of vascular wall integrity with associated IAPP deposition in the smooth muscle and arterioles of capillaries of patients with T2D and dementia . Animal models included in the same study demonstrated more microhaemorrhages, white matter injury, and cognitive deficits in animals infused with IAPP or engineered to overproduce the protein . A SNP in IAPP was demonstrated to interact with degree of PET‐imaged cortical amyloid burden, showing a significant association with decreased temporal lobe cortical thickness and cognitive decline .…”
Section: Amylin the Blood‐brain Barrier And Lymphaticsmentioning
confidence: 80%
“…The following two additional emerging hypotheses may be 'game changers' in regard to both the novel treatments of LOAD by repurposing insulin and insulin sensitizing medication and aiding in the understanding of the development and/or the continuum of progression in LOAD. Aα independent deposition in the perivascular regions and extracellular matrix, which may possibly interfere with Aβ efflux or clearance [169,170,171,172,173,174]. The amylin hypothesis involving the amyloidogenic Aα might also lead to the use of an amylin analog (pramlintide) for clinical study that has already been approved and utilized to treat type 1 and T2DM and known to improve glucose levels [175].…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%